The Origins of Settlement, Agriculture and the City State in Mesopotamia - Maisels, Charles Keith
Ph.D. Thesis presented in the Department of Social Anthropology, Faculty of Social Sciences; Supervisor: Alan Barnard; 380-382: Appendix: The Pantheon of the Sumerian City State; Available from The British Library, Document Supply Centre. Order No. D53586’85.